(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
The proximate, mineral and anti-nutritional compositions of Basella alba and Senecio biafrae were determined. The vegetables were also screened for phytochemicals and the polyphenols present in them analyzed using reverse-phase high performance liquid chromatography. The results of proximate in % were: moisture (11.75, 12.24), crude protein (19.22, 20.17), ash (20.95, 21.48), total dietary fibre (16.57, 22.51), crude fat (10.49, 13.34) and carbohydrate (21.02, 10.26). Dietary minerals were present in appreciable quantities: sodium (660, 300), potassium (7800, 1430), calcium (1050, 1150), magnesium (350, 310), zinc (41, 34), copper (0.10, 1.80), iron (1.40, 2.00), and phosphorus (20.50, 13.40) in mg/100g respectively. Lead was not detected in Basella alba but in trace amount in Senecio biafrae (0.002). Vitamins in µg/g were: vitamin A (13.21, 9.78), thiamine (315.22, 315.22), ascorbic acid (14.86, 9.85) and tocopherol (49.89, 192.38). Amino acid profile of the two vegetables showed appreciable essential: histidine (2.14, 2.27), isoleucine (3.01, 3.43), leucine (7.75, 8.85), lysine (2.92, 4.62), methionine (0.89, 0.99), phenylalanine (3.88, 4.22), threonine (2.84, 3.15) and non essential amino acids: valine (3.13, 3.71), arginine (3.97, 4.49), aspartic acid (7.32, 8.28), serine (2.09, 2.22), glutamic acid (10.15, 10.83), proline (2.24, 2.65), glycine (3.07, 3.56), alanine (3.49, 4.03), cysteine (0.79, 0.86), tryosine (2.22, 2.70). Antinutrient factors present in mg/g were: tannin (2.34, 1.45), oxalate (1.17, 0.45) and phytate (1.03, 0.08). Caffeic acid was, most aboundant phenolic acid in both vegetables (32.74, 37.51); and their flavonoid compositions were similar except for catechin which was lacking in Senecio biafrae. The nutritional and nutraceutical potential of both vegetables are good and could be exploited to promote health. Bangladesh J. Sci. Ind. Res. 52(3), 201-208, 2017